Rifampin-resistant periprosthetic joint infections are associated with worse functional outcome in both acute and chronic infection types - Baumgärtner, Tobias; Bdeir, Mohamad; Dally, Franz; Gravius, Sascha; Abd El Hai, Asseel; Assaf, Elio; Hetjens, Svetlana; Miethke, Thomas; Darwich, Ali (Diagnostic microbiology and infectious disease, 2024)
Periprosthetic joint infections (PJI) pose a significant challenge in orthopaedic surgery, often requiring extensive surgical debridement and prolonged antibiotic treatment to eliminate the causative pathogens. Rifampin, known for its potent activity against biofilms, has been crucial in managing PJI by penetrating and disrupting these formations, thereby improving treatment efficacy. In this sense, antibiotic protocols lacking rifampin have shown increased failure rates. Consequently, the development of rifampin resistance could severely influence the prognosis of PJI. The aim of this clinical study was to assess how rifampin resistance affects the functional outcome in patients with PJI. In this single-centre comparative cohort study, we systematically documented all patients who presented with a PJI during the period spanning from 2018 to 2020. Two distinct groups were established for the study: Group 1 comprised 35 patients with a PJI caused by rifampin-susceptible pathogens and group 2 consisted of 28 patients with PJI caused by rifampin-resistant pathogens. A total of 63 patients (34 females) with a mean age of 68 years and a mean follow up of 37 months were included. The examination of patient-specific parameters did not reveal any identified risk factors as influential. Patients with a rifampin-resistant pathogen underwent a greater number of surgical revisions (6.9 ± 5.1 compared to 3.59 ± 3.39, p = 0.0011) and had extended durations of antibiotic treatment (p = 0.0052). The results of the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score revealed significant differences in clinical outcome between both groups in every domain, even when stratified by acute and chronic entities. In total the WOMAC increased significantly from 21.57 ± 14.9 points in group 1 to 71.47 ± 62.7 points in group 2 (p < 0.001). The higher failure rates observed in group 2 were not statistically significant (p = 0.44). The current study demonstrates that PJI caused by rifampin-resistant bacteria are associated with a significantly worse functional outcome in both acute and chronic infection types without significantly affecting total failure rates.
Online verfügbar: 19. Juli 2024, Artikelversion: 6. August 2024
Gesehen am 25.11.2024